Arthroscopic Transfer of the Long Head of the Biceps Brachii for Anterior Shoulder Instability - Jin Tang, B.M.; Jinzhong Zhao, M.D. (Arthroscopy Techniques, 2017)
In the treatment of anterior shoulder instability, there are various conditions in which a sling effect is needed to enhance anterior stability. The traditional Latarjet procedure provides a sling effect but destroys the coracoacromial arch, which may result in superior instability. To preserve the coracoacromial arch and create a sling to enhance the anterior-inferior side of the shoulder, we introduce an arthroscopic technique to transfer the long head of the biceps (LHB) brachii. Indications of LHB transfer are patients younger than 45 years of age who participate in competitive sports, require forceful external rotation and abduction movement of the shoulder, and/or have capsule-ligament insufficiency, as well as patients 45 years o or older who have combined SLAP lesions (type II or IV). The main steps of this procedure include detaching the LHB, retrieving and braiding the LHB, creating a glenoid tunnel, placing a guide suture through the subscapularis and glenoid tunnel, passing the LHB through the subscapularis and into the glenoid tunnel, and suspension fixation of the LHB.